Core and Periphery of Information Society: Significance of Geospatial Technologies - Werner, Piotr A.; Opach, Tomasz (Quaestiones Geographicae, 2013)
The paper attempts to identify important factors significant for global information society development and to determine the significance of geospatial (geo-information) technologies. The starting point is international measures of the development level of information & communication technologies (ICT) and information society (IS). The relevance of the particular factors was defined using the general segmentation of the milieu, taking into account social, technological, economic, environmental, political, legal and ethical factors and also estimating the global spatial dimension of ICT and IS development. The diagnosis serves as the context of considerations concerning the contribution of geographers and cartographers to IS.